#1**0 **

----------------------------

x = (x^2+y^2)

y = 2(x^2+y^2 ) from the first equation, this = 2x

Sub y = 2x in to the first equation

x = x^2 + 4x^2 re-arrange

5x^2-x = 0

x (5x-1) = 0 so x = 0 and .2 sub these values into the equation (red ones) to find the corresponding 'y' values.....

ElectricPavlov Dec 22, 2019

edited by
ElectricPavlov
Dec 22, 2019

edited by ElectricPavlov Dec 22, 2019

edited by ElectricPavlov Dec 22, 2019

edited by ElectricPavlov Dec 22, 2019

edited by ElectricPavlov Dec 22, 2019